Sistemas exoplanetários - Bezerra, Brandon Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Beyond the Solar System there are more than 3000 stellar systems composed of since dwarfs to supergiant stars, orbited by more than 4000 exoplanets divided in several types, small and rocky, giant and gaseous, some of which are not seen in the Solar System. Several methods are used in order to detect and confirm these worlds, each one with its own advantages. Successful space missions use some of them, aiming mainly to detect certain effects caused by exoplanets orbiting their systems’ stars. There are lone planets in small systems, in systems with more than one star, with several planets, or even orbiting different bodies. Like Earth, there are those within their stars’ habitable zone, region where water exists in its liquid form, what is usually related to possible life forms. In the same way as in the Solar System, there may be other objects than stars and planets, they are the exomoons, exocomets, asteroids and exorings, some of which are already confirmed, while others are still candidates. Detecting and confirming objects that were never seen before is a difficult and delicate task, but with advanced technology in the near future there will be more precise equipments able to characterize systems and bodies which are unable to be observed nowadays. This work aims to clarify frequent terms and concepts regarding exoplanetary systems, present important data and a few examples of exoplanets and extrasolar objects.

Além do Sistema Solar existem mais de 3000 sistemas estelares compostos por estrelas desde anãs até supergigantes, orbitadas por mais de 4000 exoplanetas de variados tipos, pequenos e rochosos, gigantes e gasosos, alguns desses tipos não vistos no Sistema Solar. Para detectar e confirmar esses mundos são empregadas uma série de métodos, cada um com suas vantagens. Alguns deles utilizados por bem-sucedidas missões espaciais, cujo objetivo é principalmente detectar efeitos causados por exoplanetas orbitando as estrelas de seus sistemas. Há planetas solitários em sistemas pequenos, em sistemas compostos por mais de uma estrela, por vários planetas, ou mesmo orbitando objetos diferentes. Como a Terra, existem aqueles na zona habitável de suas estrelas, região onde a água pode existir em seu estado líquido, condição associada à possíveis formas de vida. E da mesma forma que no Sistema Solar, existem corpos além das estrelas e planetas, são as exoluas, os exocometas, asteroides e exoanéis, alguns deles já confirmados e outros ainda candidatos. A primeira detecção e confirmação de objetos nunca vistos antes é difícil e delicada, mas com o futuro avanço tecnológico e o surgimento de equipamentos mais precisos, poderá ser feita a caracterização de sistemas e corpos que não são capazes de ser observados hoje. O presente trabalho visa elucidar termos e conceitos frequentes no tema de sistemas exoplanetários, apresentar dados importantes e alguns exemplos de exoplanetas e objetos extrassolares.
Exoplanetary systems
Keywords: Exoplanets; Exomoons; Extrasolar systems; Exoplanetas; Exoluas; Sistemas extrassolares; Sistema solar; Astrometria